2019
DOI: 10.14295/transportes.v27i2.1728
|View full text |Cite
|
Sign up to set email alerts
|

Compreensão da formação de NO2 proveniente das operações de transporte urbano e suas relações com agentes causais

Abstract: Os problemas oriundos da mobilidade urbana estão relacionados ao crescimento acelerado e não planejado das cidades, à distribuição espacial das atividades, ao crescimento expressivo do uso do automóvel, as deficiências do transporte público e a ocorrência de impactos negativos nos âmbitos sociais e ambientais, tendo como um dos principais impactos a concentração de NO2. Dessa forma, o presente trabalho tem por objetivo avaliar a influência dos fatores (gabarito das edificações, uso do solo e volume de tráfego)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
1
1
Order By: Relevance
“…For each route, the average value of all collection points in each campaign was considered, considering the radius of influence of the pollutant dispersion in the samplers, whose results (in µg/m³/h) are shown in Figure 4. that the values are within the limits found in other studies carried out in the city of Fortaleza (DIAS, 2018;RIBEIRO et al, 2019). Although the values found are lower than those established by CONAMA Resolution 491/2018, the comparison of the results presented here cannot be rigorously compared to the normative, as the sampling method used here differs from that established by the resolution.…”
Section: Discussion Of Resultscontrasting
confidence: 44%
See 1 more Smart Citation
“…For each route, the average value of all collection points in each campaign was considered, considering the radius of influence of the pollutant dispersion in the samplers, whose results (in µg/m³/h) are shown in Figure 4. that the values are within the limits found in other studies carried out in the city of Fortaleza (DIAS, 2018;RIBEIRO et al, 2019). Although the values found are lower than those established by CONAMA Resolution 491/2018, the comparison of the results presented here cannot be rigorously compared to the normative, as the sampling method used here differs from that established by the resolution.…”
Section: Discussion Of Resultscontrasting
confidence: 44%
“…In the study, it was found that during the school period there was an increase of around 40% in the average pollutant compared to the period without classes when the flow of vehicles is reduced, which indicates the influence of internal traffic on air quality. Dias (2018) and Ribeiro et al (2019) presented studies aimed at assessing air quality and its relationship with transport systems in the city of Fortaleza -CE, using passive NO2 sampling. The results obtained by the works showed that the range of variation found for the pollutant was between 0.19 μg/m3.h-1 to 65 μg/m3.h-1, showing that the values obtained were directly related to the volume of traffic, the use of the land and the functional classification of the roads.…”
Section: Air Quality and Monitoringmentioning
confidence: 99%
“…As amostragens de NO2, SO2 e MP10 foram realizadas com a usina inativa (sem produção) e em operação. NO2 e SO2 foram coletados por amostragem passiva seguindo a metodologia proposta por Ribeiro et al (2019). Impregnaram-se filtros de celulose (25 mm de diâmetro) com 100 µL de solução absorvente, para NO2 utilizou-se uma solução alcoólica de KI 0,5 M e KOH 0,2 M, e para SO2 uma solução aquosa de Na2CO3 0,01 mol.L -1 .…”
Section: Materiais E Métodosunclassified